Anteseden Brand Trust, Product Quality, Social Media paradigms Terhadap Purchase Intention Pada Beauty Industri Di Indonesia - rahmawati, Rr Yuliana; Kurniawati, Kurniawati (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
This research was formed because there are many make up or skincare brands and their growth is increasing. The beauty industry has been a very interesting segment in recent years. Lots of people are starting beauty businesses starting from skincare, makeup, and others, both online and offline. Competition between local brands and foreign brands is increasingly fierce. This can be seen from the number of beauty products registered in Indonesia. In this case, competition is created so that the product is superior to competitors, especially local brands. The aim of this research is to find out whether the strategy used is appropriate for consumers repurchase decisions. The population of this research is women who use and buy local beauty brands with the sample used being purposive sampling. The sample obtained was 180 respondents. This research provides results that brand trust does not have a positive effect on attitude. Meanwhile, product quality and social media paradigms have an influence on attitude. And attitude has a positive effect on brand loyalty and purchase intention. Brand loyalty also has a significant positive effect on purchase intention